The impact of endoscopic biliary drainage on the nutritional status of patients with malignant perihilar or periampullary biliary strictures - Acharki, Mohamed; boussenna, Imane; Essadni, Yasmine; Kabbaj, Nawal; Bour, Abdellatif (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Malignant biliary obstruction is the cause of complications affecting nutritional status. Biliary drainage with stenting is the recommended palliative treatment for these patients. This study assesses the impact of biliary drainage on nutritional status by comparing patients before and after the procedure. Methods: This study evaluates, through a retrospective analysis, the variation in patients nutritional status before and after biliary drainage wether in perihilar or periampullary strictures We studied 200 patients with tumoral biliary stricture who underwent endoscopic biliary drainage. Demographic, anthropometric and clinical data were collected before and after drainage in two stages (1 and 3 months). Statistical analysis was performed using SPSS26 software. Results: The results showed a significant increase in mean weight, reaching 59.27kg after 3 months (p<0.05). Mean BMI also increased significantly, (20.39kg/m2 after 3 months (p<0.05)). NRI decreased significantly after drainage. 35.17% still had severe undernutrition after 3 months (p<0.05). Mean ALB increased significantly, (34.52g/l after 3 months (p<0.05)). Mean BT also decreased significantly, (15.03mg/l after 3 months (p<0.05)). However, the decrease in CRP was not statistically significant. The WHO performance score showed significant improvement, with 25% of patients presenting with Stage 0 after 3 months. Pruritus and jaundice were absent in 100% of patients after 3 months. When comparing the perihilar and periampullary stenosis groups, no significant differences were observed for any of the parameters studied. Conclusions: The results suggest that endoscopic biliary drainage significantly improves the nutritional and clinical status of these patients, irrespective of the location of the obstruction.